The Influence of Social Media Marketing and Brand Awareness on Purchasing Decisions with Brand Image as a Mediating Variable in Kopi Kenangan - Putri, Dinda Arisma; Nurhayati , Nurhayati; Firdaus, Firdaus (Economics and Business International Conference Proceeding, 2024)
This research aims to test the influence of social media marketing and brand awareness on purchasing decisions with brand image as a mediating variable at Kopi Kenangan DP Mall Semarang. The population in this study were consumers who had purchased Kopi Kenangan, DP Mall Semarang. By using a sample of 104 respondents. The analysis method for this research uses outer model and inner model analysis using the SmartPLS (Partial Least Square) Version 4.0 data processing tools.The results of this study indicate, based on hypothesis test, social media marketing variables has a positive and insignificant effect on brand image, brand awareness has a positive and significant effect on brand image, social media marketing has a positive and significant effect on purchasing decisions, brand awareness has a positive and insignificant effect on purchasing decisions, brand image has a negative and insignificant effect on purchasing decisions, and brand image as a mediating variable has no direct effect on social media marketing and brand awareness on purchasing decisions.